1995
DOI: 10.1177/016502549501800102
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Childhood Behaviour Problems, Maternal Employment, and Day Care in a Rural Norwegian Community

Abstract: A longitudinal study followed 120 children and their families of a rural cohort from the preschool period until 10 years of age. The prevalence of behaviour problems was similar to that found in other studies in different countries, except at the age of 10, when a modification of the cutoff point was indicated for the parental report measure. The prevalence of behaviour problems was initially influenced by gender and intelligence test scores. Day care centre experience at a later age was associated with lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 37 publications
3
26
2
4
Order By: Relevance
“…Previous studies have found that children with extensive child care experience showed more non-compliance and problem behavior (Bates et al, 1994;Belsky & Eggebeen, 1991;Borge & Melhuish, 1995;NICHD Early Child Care Research Network, 1998), and some studies have reported better adjustment in children when they had few changes in care arrangements (McCartney et al, 1997;NICHD Early Child Care Research Network, 1998). Our results indicate that it may not be daily stability in care that accounts for this association, nor long-term continuity in care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that children with extensive child care experience showed more non-compliance and problem behavior (Bates et al, 1994;Belsky & Eggebeen, 1991;Borge & Melhuish, 1995;NICHD Early Child Care Research Network, 1998), and some studies have reported better adjustment in children when they had few changes in care arrangements (McCartney et al, 1997;NICHD Early Child Care Research Network, 1998). Our results indicate that it may not be daily stability in care that accounts for this association, nor long-term continuity in care.…”
Section: Discussionmentioning
confidence: 99%
“…All night care centers in this study had passed governmental standards and attempted to ensure that the natural circadian rhythms for children, such as sleeping, eating, and playing, were well maintained. Several relatively recent large-scale, center-based childcare studies conducted outside Japan have documented relations between early and/or extensive childcare experience, noncompliance, and problem-behavior, even after controlling for selection effects (Bates et al, 1994;Baydar & Brooks-Gunn, 1991;Belsky & Eggebeen, 1991;Borge & Melhuish, 1995;Park & Honig, 1991;Vandell & Corasaniti, 1990). Divergent results emerged from the current investigation, which found little evidence that the amount of time children spent in non-parental care in the first 2 or 3 years of life is, in and of itself, systematically related to children's self-control, compliance, or problem behavior by the time they reach the school-age years.…”
Section: Discussionmentioning
confidence: 99%
“…Em uma amostra de grande porte na Dinamarca, mais horas em creche aos 3 anos foram associadas a grande quantidade de relatos por mães, sobre problemas comportamentais, aos 7 anos (GUPTA; SIMONSEN, 2009). Na Noruega, em um estudo que considerou o emprego materno como referência para o atendimento em creche, houve associações com o relato de professores sobre problemas de comportamento aos 10 anos, mas não com o relato de mães sobre esse tipo de problema, dos 4 aos 7 anos (BORGE; MELHUISH, 1995). Em estudo recente de amostra nacional com mais de 70 mil crianças na Noruega (ZACHRISSON et al, 2013) não se encontrou evidência de associação entre quantidade de cuidados não materno e problemas comportamentais.…”
Section: Tempo De Atendimento E Desenvolvimento Social E Emocionalunclassified